Towards a Stakeholder-Based Map on Parental Participation in Genoese School Life - Freddano, Michela (International Journal about Parents in Education, 2023)
The aim of this article is to examine the partnership among home, school and community from a micro-sociological point of view deepening the concept of parental involvement in school life from the stakeholder standpoint. Qualitative approach has been adopted. Secondary-source data have been collected on the institutional background and the field research included interviews on a selected non probabilistic sample composed by parents, teachers, experts, school heads, decision-makers and members of parental associations from the Genoese community. In addition to interviews, participant observation of formal and non formal meetings between parents and teachers and principals has been undertaken in some primary and middle schools of Genoa. The main findings are presented in the form of descriptive analysis, illustrating the perceptions of several stakeholders interviewed. Although they are not representative of the whole population, they proved to be helpful to map the dimensions of parental involvement in school life.